An Amalgamated Approach of Fuzzy Logic and Genetic Algorithm forBetter Recruitment Process - Khandelwal, Anju; Agrawal, Ashish (Discoveries in Agriculture and Food Sciences, 2015)
The recruitment process in any departments or organizationsis usually decided by traditional criteria. In today’s scenario, every organization wants to have best employees for their work. Many organizations are used to have separate departments to solve this purpose. But sometimes the recruitment process gets affected by human perceptions, beliefs, pat experiences, feelings, personal relations etc..So, for making recruitment process more automatic and accurate, various authors have proposed their solutions with Hungarian method. In this paper, authors are proposing a method of recruitment by the use of fuzzy triangular number and genetic algorithm with Hungarian method. After performing the first stage (written test) of recruitment with fuzzy triangular number and Hungarian method, the later stages are accomplished with linguistic variables and final recruitment is performed by the use of genetic algorithm.